Pengaruh Kualitas Obat dan Kualitas Layanan Islami terhadap Loyalitas Konsumen pada Apotek Nora di Kota Metro - Yusup Saputra; Finny Ligery; Ahmad Muslimin (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to examine the influence of drug quality and Islamic service quality on consumer loyalty in pharmacies. The novelty of this research lies in combining functional factors, such as drug quality, with ethical values based on Islamic principles, including amanah, ihsan, sidq, and justice. This study uses a quantitative approach. Data were collected from pharmacy consumers through questionnaires using purposive sampling. The data were analyzed using multiple linear regression. The results show that drug quality has a positive and significant effect on consumer loyalty. This indicates that safe, effective, and high-quality drugs can increase consumer trust, leading to repeat purchases and recommendations. In addition, Islamic service quality also has a positive and significant effect on consumer loyalty. Values such as honesty, trust, fairness, empathy, and good service create comfort and strengthen emotional and spiritual connections with consumers. Furthermore, drug quality and Islamic service quality together play an important role in building consumer loyalty. However, this study is limited to pharmacy services in a specific location. Therefore, the results cannot be generalized to all pharmaceutical sectors or other regions.